2021
DOI: 10.1027/2698-1866/a000017
|View full text |Cite
|
Sign up to set email alerts
|

A German Adaptation of the Prosociality Scale

Abstract: Abstract. Introduction: This paper presents a German translation of the 16-item Prosociality Scale. We analyzed its factor structure based on theoretical assumptions regarding the inclusion of empathy as one element of prosociality or as its underlying construct. Methods and Results: We translated the items into German taking into account both the English and the Italian item wordings. The scale's factor structure was analyzed with three models testing (1) unidimensionality, (2) a four-factor structure with fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Data from the What’s NEXT? Study were already used by Fassbender et al (2021), Fassbender and Luhmann (2021), Kritzler et al (2021), and Luhmann et al (2020), but these publications did not investigate stability or change of perceived event characteristics. Data collection was approved by the local ethics committee of Ruhr University Bochum (Protocol 422: “Examining characteristics of adverse events as predictors of character growth”).…”
Section: Methodsmentioning
confidence: 99%
“…Data from the What’s NEXT? Study were already used by Fassbender et al (2021), Fassbender and Luhmann (2021), Kritzler et al (2021), and Luhmann et al (2020), but these publications did not investigate stability or change of perceived event characteristics. Data collection was approved by the local ethics committee of Ruhr University Bochum (Protocol 422: “Examining characteristics of adverse events as predictors of character growth”).…”
Section: Methodsmentioning
confidence: 99%
“…However, if participants happened to experience the same event twice (e.g., “failed an exam” may occur twice within a year of assessment), we only included the first description of this event. Data from Samples 1 to 4 have already been used for other research projects (Fassbender et al, 2021; Fassbender & Luhmann, 2021; Haehner, Kritzler et al, 2021; Luhmann et al, 2021) but have not yet been used to compare different events or types of raters.…”
Section: Methodsmentioning
confidence: 99%
“…We use the full sample of N = 446 observations. Further information about data collection, exclusion criteria for the original study, and the analysis scripts of the original study can be found together with the data in the OSF repository of Fassbender and Luhmann (2021).…”
Section: Refa Demonstration On Simulated Datamentioning
confidence: 99%
“…As parallel analysis suggests three factors, we will conduct a REFA with three latent factors. A three-factor solution was also considered by Fassbender and Luhmann (2021) in their supplemental material. They also discuss other factor solutions and found a four-factor model or rather a model with a general factor and three fits best.…”
Section: The Regsem Packagementioning
confidence: 99%
See 1 more Smart Citation